CALOHEE - Comparing Learning Outcomes in Higher Education in Europe - Assessment Framework How to verify acquired learning outcomes - Alfredo Soeiro (2021)
DEPARTMENT OF MECHANICAL ENGINEERING ASSESSMENT IN ENGINEERING EDUCATION: A PEDAGOGICAL APPROACH AICTE APPROVED SHORT TERM TRAIINING PROGRAM (STTP) DETAILED SCHEDULE PHASE 3-04.01.2021-09.01.2021 DATE DAY 10.30AM-12.30PM 12.30-01.30PM 01.30-03.30PM 04.01.2021 MONDAY Dr Kapil Kadam-IIT Bombay Assessment: What, Why, How and Online" LUNCH BREAK Dr NC Shivaprakash-IISC Bangaloru -Challenges in good learning and assessment 05.01.2021 TUESDAY Dr Pradeep Kumar Choudrey-Jawaharlal Nehru University, NewDelhi Assessment in Engineering Education: Where do we fail and Why? Dr G Janardhanan- NITTR Chennai Fundamentals of Assessment and Characteristic of good assessment, item analysis with case study linking with academic and role of feedback using rubrics 06.01.2021 WEDNESDAY Dr S Rajarajan- Sairam Institute of Technology Impact analysis of assessing Industrial Visit, industrial sponsored laboratories and internship Ms Jayachitra- KAHE, Coimbatore Role of Assessment in Teaching & Learning 07.01.2021 THURSDAY Dr BS Pabla-NITTR Chandigarh Development and evaluation of Assessment Plan Assessment and Evaluation in Outcome Based Education (OBE) environment Dr Alfredo Soeiro- Universidade do Porto, Portugal Role of assessment, Selecting the right methods of assessment for your course, constructive alignment and role of feedback 08.01.2021 FRIDAY Dr Thayyaba Khatoon-Malla Reddy College of Engineering & Technology, Hyderabad Formulation of good assessment questions, developing rubrics helps with providing feedback Prof. P Gopala Krishna Achieving Academic Excellence-A Case Study of NIRF 09.01.2021 SATURDAY Dr T Lakshmanan- SRM Institute of Science & Technology Significance of Question Papers in Assessment Dr Atasi Mohanty-IIT Kharagpur role of assessment in enhancing students' performance and motivation, Selection of right methods for our own course and feedback